APPLICATION OF INFORMATION TECHNOLOGY INTEGRATED SYSTEM TO IMPROVING THE QUALITY AND FINANCIAL PERFORMANCE - I Putu Gde Sukerta; Gede Sri Darma (Universitas Pendidikan Nasional, 2014)
The purpose of this study was 1) to determine and analyze the implementation and useof information systems technology in the integrated financial information and data processingservices that result in hospital inefficiency and decrease operational performance(management control). 2) To determine and analyze the impact of Integrated InformationSystem Technology to the performance as well as improved quality of service FinanceDepartment (Mobilization Fund) 2) To identify and analyze the factors that constrain andsupport the implementation of an integrated system of information technology in improving theperformance and quality of service parts Finance (Mobilization Fund) to the customer.The results found that iplementasi integrated information system in Sanglah GeneralHospital Center which has lasted from the 2000s to the present in dasrnya has been goingaccording to the plan set out in the master plan for the development of integrated informationsystems at General Hospital Center. In the implementation of an integrated information systemis currently still searching for the best format because there are many drawbacks encounteredin the design of the integrated information system implementation. Also encountered in thisstudy that the implementation of an integrated information system, the units appears to be stillrunning their own separate themselves so visible. This means that the implementation ofintegrated information systems tend to be at the start of the aspects of technology instead ofinstitutional aspects. Other findings generated relating to the above conclusion is fruitionGeneral Hospital Center in order to decentralize information, achieving accuracy andcompleteness of information, prevention of Informat on a particular group has been realizedin the implementation of integrated information systems at General Hospital Center..Keywords: technology information systems